Analisis Kinerja Badan Pengelolaan Keuangan Pendapatan dan Aset Daerah (BPKPAD) Kota Binjai - Muhammad Fariz Adhitya; Juliana Nasution (Jurnal Multidisiplin Dehasen (MUDE), 2022)
The purpose of this research is to obtain an overview of the performance of regional property managers, the Land and Finance Agency of Binjai City (BPKPAD). As the Regional Treasurer, BKPAD is a technical organization that is responsible for receiving regional revenues and financing regional needs through the Ministry of Regional Finance. The presence of the regional treasury allows the regions to regulate the availability of sufficient funds to fund regional expenditures. The Regional Treasury Department can also be used to find out what the wealth of an area is. The regional treasury itself is also included in the comparative balance, which is part of the financial statements. The previous cash management survey received regional revenues and used the funds paid for regional expenditures. The administrative guidelines for the implementation of the Binjai City APND stipulate that the procedures for receiving and paying cash are handled directly by the Ministry of Finance, and the Ministry of Finance has carried out its functions in accordance with these guidelines. In general, the performance of Binjai City BPPKAD Asset Management is currently not good and still not optimal. This can be seen from the metrics used to measure the current performance of BPPKAD Asset Management: accountability, transparency, and profitability. Efficiency and effectiveness need to be improved in order to increase APBD revenues to provide regional finance.